Investigation Of The Performance And Emission Characteristics Of Diesel Engine Fueled With Biogas-Diesel Dual Fuel - Melkamu, Genet (ASTU, 2020)
Diesel Engines Are The Most Reliable And Efficient Energy Conversion Devices With Higher Popularity And Wider Usage. This Resulted In Increased Utilization Of Fossil Fuels In The Transport Sectors. The Resources Of Fossil Fuels Are Depleting And Their Prices Are Increasing Day By Day, Negatively Affecting The Economy Of Developing Countries Which Are Dependent On The Importation Of Petroleum Fuels. However, The Emission From The Burning Of Fossil Fuels Harming The Global Environment. These Challenges Led To Search And Utilize Alternative Fuels, Which Are Attractive Because Of Their Environmentally Friendly Nature. The Present Study Covers The Utilization Of A Gaseous Alternative Fuel, Raw Biogas, In A Diesel Engine. Biogas Alone Cannot Run A Diesel Engine, Because Gaseous Fuel Cannot Burn By Compression. It Can Be Supplied To The Ci Engines In Dual Fuel Mode By Using An Airbiogas Mixer Device. In This Work, It Is Aimed To Investigate The Performance And Emission Characteristics Of A Biogas-Diesel Dual Fuel Mode Diesel Engine By Employing A Venturi Gas Mixer Device For Providing A Homogeneous Mixture. The Experiment Was Conducted On A Single-Cylinder, Four-Stroke, Air-Cooled And Naturally Aspirated Direct Injection Diesel Engine (Tbmc3-02) With A Maximum Power Output Of 2.2kw By Varying Engine Load At A Constant Speed Of 1500rpm. The Diesel Was Injected By Conventional Injector Setup And The Biogas Was Inducted Through The Intake Manifold With Air At Different Flow Rates Of 2l/Min, 4l/Min And 6l/Min. The Performance And Emission Characteristics Of The Engine Operated By Dual-Fuel Mode Were Experimentally Investigated, And Compared To Diesel. The Results Indicated That Biogas Inducted At A Flow Rate Of 2l/Min Was Found To Have Better Performance And Lower Emission, Than That Of The Other Flow Rates. On The Other Hand, Dual-Fuel Mode With A Biogas Flow Rate Of 2l/Min Showed An Average Reduction In Brake Power, Brake Torque And Bte Of 2.81%, 3.65% And 15.94% Respectively And An Average Increment Of 11.82% In Bsfc As Compared To Diesel. Whereas An Increment In Co, Co2 And Hc By 10.18%, 12.8% And 6.01 % Respectively And An Average Reduction In O2 And Nox Emissions By 7.01% And 19.91% Respectively As Compared To Diesel. The Diesel Replacement Ratio Varies From 19.56% To 7.61% At Zero And 80% Engine Load With Biogas Energy Share Of 39.6% And 16.59% Respectively.
Keywords: Alternative Fuel, Biogas, Diesel Engine, Dual-Fuel, Venturi Gas Mixer .